2019
DOI: 10.3390/drones3020035
|View full text |Cite
|
Sign up to set email alerts
|

Drone Laser Scanning for Modeling Riverscape Topography and Vegetation: Comparison with Traditional Aerial Lidar

Abstract: Lidar remote sensing has been used to survey stream channel and floodplain topography for decades. However, traditional platforms, such as aerial laser scanning (ALS) from an airplane, have limitations including flight altitude and scan angle that prevent the scanner from collecting a complete survey of the riverscape. Drone laser scanning (DLS) or unmanned aerial vehicle (UAV)-based lidar offer ways to scan riverscapes with many potential advantages over ALS. We compared point clouds and lidar data products g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 34 publications
1
78
0
Order By: Relevance
“…A recent study [10] comparing ALS, TLS, and ULS concluded that ULS fills the gap between TLS and ALS by enabling both extensive coverage of a project area that is difficult to achieve with TLS as well as the acquisition of sufficient point density for describing small morphologies missed in ALS, which is vital for landslide monitoring applications. Additionally, Resop et al [4] also compared ULS to ALS in order to show the ability of ULS to capture important topographic features. In the USGS Lidar Base Specification (v1.3), for the highest quality level (QL0), the USGS suggests an aggregate nominal point spacing of ≤ 0.35 m, and an aggregate nominal point density of ≥ 8 points/m 2 [11].…”
Section: Uls Accuracy and Data Qualitymentioning
confidence: 99%
“…A recent study [10] comparing ALS, TLS, and ULS concluded that ULS fills the gap between TLS and ALS by enabling both extensive coverage of a project area that is difficult to achieve with TLS as well as the acquisition of sufficient point density for describing small morphologies missed in ALS, which is vital for landslide monitoring applications. Additionally, Resop et al [4] also compared ULS to ALS in order to show the ability of ULS to capture important topographic features. In the USGS Lidar Base Specification (v1.3), for the highest quality level (QL0), the USGS suggests an aggregate nominal point spacing of ≤ 0.35 m, and an aggregate nominal point density of ≥ 8 points/m 2 [11].…”
Section: Uls Accuracy and Data Qualitymentioning
confidence: 99%
“…A combination of terrestrial and airborne LiDAR with high spatial resolution RS-RGB data are crucial RS technologies for monitoring and assessing stream bank conditions [168,174,241]. UAV-based laser scanning in combination with other sensor technologies have also been used increasingly more for monitoring and modeling riverscape morphometric and vegetation traits [242][243][244].…”
Section: Flood Hazardmentioning
confidence: 99%
“…It is also noteworthy to recognise the increasing use of UAV-based LiDAR, which is rapidly becoming a practical alternative to UAV-based imagery in situations where penetration of water of plant canopy is desired in order to image underlying topography [99]. Although drone laser scanning technology (e.g., LiDAR) is currently more commonly employed by non-UAV remote sensing platforms (e.g., manned aircraft and satellites), increasing technological development of these sensors will improve accessibility of this technology as a surveying option and thus greatly improve its utility for UAV application into the future [99].…”
Section: Analysis and Reporting Of Restoration Monitoring Datamentioning
confidence: 99%